The Effect of Regional Development on The Sustainability of Local Irrigation System (A Case of Subak System in Badung Regency, Bali Province) - I Putu Sriartha; Suratman Suratman; Sri Rum Giyarsih (Forum Geografi, 2015)
This study was aimed at investigating the sustainability of subaks in the dynamics of regional development in the metropolitan area of Badung Regency, Bali Province. The data on subak sustainability were collected by using survey method in 69 subaks as the units of analysis, and the secondary data on the factors of regional development were collected by using document recording method. The data were analyzed by using quantitative decriptive technique, Analytical Hierarchy Process (AHP), and multiple linear regression. The results showed that the spatial distribution of subak sustainability levels forms cluster pattern with different dominations in short-, trantitional- and long- distance zones from the  tourism center. The components/elements of Tri Hita Karana (THK) that constitute the first priority in subak sustainability protection are wet land conversion control and guarantee for irrigation water adequacy. It was found that five factors ot regional development have a strong influence on subak sustainability with 87.8% contribution, and the rest (12.2%) is acounted by other factors outside the scope of this study.